Analisa Harga Pokok Produksi dalam Menentukan Harga Jual Menggunakan Metode Full Costing: (Studi Kasus Ayam Gebuk Sambalado – Tangerang) - Arum Prihatini; Fransiska Fransiska (Jurnal Mutiara Ilmu Akuntansi, 2024)
Micro, small, and medium-sized enterprises (MSMEs) are profitable businesses that are owned by people or corporate entities that operate to satisfy personal needs and ensure their existence. Calculating and analyzing manufacturing expenses in order to establish the selling price of fried chicken goods is the goal of this study. The full cost method is used to achieve this. Using a quantitative approach, this research investigates the elements that influence selling prices. This research uses direct observation of objects and interviews with owners to obtain precise data. According to our observations and interviews with Mr. Stefanus (36), owner of the Ayam Gebuk Sambalado MSME, the business still uses conventional methods to calculate the manufacturing cost. This research uses the full costing method to make information on the cost of production more accurate. This is predicated on a comparison of the whole costing technique and the business method for determine cost of items created, which demonstrates that the final cost of goods manufactured differs significantly. This happens because business owners don’t know how to calculate the correct cost of production, so they don’t include costs correctly in the price calculation.